EKSPLORASI STRATEGI MODEL PENGUKURAN KINERJA SDM PEMDA KOTA MALANG DAN BATU UNTUK PEMBANGUNAN BERKELANJUTAN: Pengukuran Kinerja SDM, Pemerintah Daerah, Pembangunan Berkelanjutan, Evaluasi Kinerja, Model Strategi, Keberlanjutan Kebijakan - Hidayat, Imam; Ayu Dewi Novitawati, Retno; Jayhuman, Hubban (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2025)
Sustainable development is a national priority that requires effectiveness and efficiency in human resource management in the government sector. Malang and Batu, as regions with significant economic contributions, require comprehensive and adaptive human resource performance measurement strategies. Therefore, this study aims to explore a model for measuring local government human resource performance to support sustainable development. This study uses a quantitative approach. The quantitative approach is conducted through a survey of local government employees to measure the effectiveness of the existing performance system and analyse the relationship between HR performance and sustainable development indicators. The results of this study indicate that an effective performance measurement system is a vital instrument in achieving sustainable development goals that integrate economic, social, and environmental aspects holistically. The implementation of a comprehensive human resource performance measurement system has proven to enhance accountability, transparency, and the performance of government officials in implementing sustainable development programmes, while also creating an effective control mechanism to ensure alignment between organisational objectives and the sustainable development agenda.